Computer-aided process planning based on automatic fuzzy comprehensive evaluation - Tang, W; Gu, L Z; Guo, H (Proceedings of the Institution of Mechanical Engineers. Part B, Journal of engineering manufacture, 2010)
Abstract There is strong contradiction in the traditional evaluation of processes in terms of diversity of manufactured goods, discreteness of manufacturing processes, complexity of the environment of manufacture, and variability of the market. It is essential to meet the need for an automatic, time-saving, accurate, and optimal evaluation of processes. The current study was aimed at fuzzy auto-evaluation, taking the processes for the parts as (a) subject investigated, (b) structuring evaluation system, and (c) method of processes in computer-aided production planning (CAPP) based on fuzzy mathematics. On analysis and comparison, the automatic fuzzy comprehensive evaluation system was built based on the following factors: set, the weight set and assessment set, and the single factor: proposed comprehensive fuzzy evaluation. The membership degree was determined with fuzzy statistics, and the weight of various factors was determined by the fuzzy consistent matrix. A combination of theoretical analysis, practical experience, goals of evaluation, and factors set for processes was accomplished by extracting the factors that impacted evaluation of processes; weight set was established based on different weights that each factor impacting on the extent of technology programs gave; the assessment set was gained with a factor matrix which the expert group provided for every factor; the fuzzy evaluation matrix was obtained with a matrix calculation according to the model M (∧, ∨). The process grade was determined according to the principle of maximum membership degree. The process evaluation would automatically be realized through the evaluation system with the VC++ program after weights of various factors from the experts in the field were added. The optimum process was eventually obtained by comparing the grades of these processes. Three feasible processes of a disc-like component, as an example, were evaluated through this evaluation system, realizing the automatic evaluation of processes and obtaining the best process.